The oil game : the struggle between stakeholders in the case of oil and gas development on the Norwegian continental shelf outside Lofoten and Vesterålen - Johansen, Kristine Vollnes (Universitetet i Tromsø, 2008)
Lofoten and Vesterålen is an important fisheries area with traditions for this dating back hundreds of years. At the same time, it has been pointed out as a prospective oil and gas area. The oil industry is currently extending its activities and moving northwards from the North Sea into the Norwegian Sea and the Barents Sea. This has made the seas off Lofoten and Vesterålen a conflict zone. The integrated management plan put a temporary lid on petroleum activity in Nordland VI, Nordland VII, and Troms II until 2010 when the management plan will be up for revision. The topic of this thesis is the conflicts which are now evolving in the region over future developments. The thesis tries to identify the main stakeholders, their arguments and positions, and the strategies they employ to gain support for their views and interests. The game that is played over oil in Lofoten and Vesterålen is analysed in terms of power and conflict. The role of the mass media is also taken into account. The study is based on both primary and secondary data sources. Interviews have been conducted and newspaper editorials, articles, and previous research have been investigated. The thesis shows that there are many stakeholders involved – the oil industry; the fishing industry; the tourism industry; local, regional and national politicians; environmentalist organisations; the media, etc. There is a conflict between different resource-based industries as well as other groups and interests that have a stake in the future development of the region.